Grey-based Taguchi method for optimisation of hot forging of connecting rod. (2016) - Equbal, Md Israr; Ohdar, Rajkumar; Equbal, Azhar; Sood, Anoop Kumar
In this paper, three dimensional finite element analysis has been carried out using FEM-based DEFORMTM 3D software on hot forging of connecting rod. The influence of design parameters and process parameters are investigated for the responses like effective strain rate and forging load during forging operation. In order to optimise both the responses simultaneously, grey relational analysis (GRA) embedded with Taguchi method is employed. Grey relational grade is used as a performance index to determine optimal setting of process parameters for both the responses simultaneously. Analysis of variance (ANOVA) is employed to determine significant parameters. Process parameters such as flash thickness, flash width, and corner radii are found to be the most significant parameters affecting grey relational grade. Optimal process setting leading to a higher effective strain rate with the least forging load has been verified through a confirmation experiment for validation of the results. [Received 15 October 2015; Revised 25 February 2016; Accepted 13 March 2016]